Mexico : Arrangement Under the Flexible Credit Line and Cancellation of the Current Arrangement; Staff Report; Staff Supplement; and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2010)
This paper discusses the Arrangement for Mexico Under the Flexible Credit Line (FCL) and Cancellation of the Current Arrangement. The recent upward trend in output in Mexico is expected to continue, leading to projected growth of 4 percent for 2010. Financial inflows are projected to gradually resume, reflecting a normalization of global liquidity conditions. IMF staff assesses that Mexico meets the qualification criteria for access to FCL resources and recommends approval of an FCL arrangement for Mexico of SDR 31.528 billion for a period of 12 months.